Revitalizing roles and functions of mosques in Kuala Lumpur / Nur Athirah Khalit - Khalit, Nur Athirah (2011)
This dissertation is a study on the original roles and functions of a mosque in comparison to the current mosques in Malaysia focusing on the mosques in Kuala Lumpur City centre. Mosque is an important building in Islam that represents the establishment and creates the characteristic of Muslim society. A survey of the literature on mosque suggests two different ideas of the mosques which are as a House of God and a Community Development Centre. Due to its function as community development centre, Kuala Lumpur City Centre has been chosen for the scope of study given that it was the largest city in Malaysia that have high rate of population with wide range of roles, functions, and features as centre of community development in Malaysia. The objectives of the study are; to identify and investigate the roles and functions of mosques in Islam in developing the community, to analyze and study current management of the mosque, and to discover opportunities in the effort to enliven the mosques institution. A proper research methodology was adopted for this research in order to achieve the objectives. The methodologies include literature reviews, case studies, observations and interviews. There are three case studies that have been chose for the purpose of this research which are; Jamek Mosque, Kampung Baru, As-Syakirin Mosque, KLCC, and Khalid Ibnu Al-Walid Mosque, Jalan Padang Tembak. A comparison between roles and functions of each case study with the ideal mosque during Prophet’s (p.b.u.h) time will be analyzed. From the analysis, it can be said that current mosques in Malaysia are still practicing relatively the same roles as it used to be during the time of Prophet (p.b.u.h), but in smaller scopes and target groups due to inadequate facilities to supports its proper functions. Consequently, even though the need to revitalize the roles and functions of mosque is not debatable anymore, however there are still needs to discover opportunities to prosper the mosque. This dissertation has also suggested some recommendations to improve the roles and functions of mosque in Malaysia. As a conclusion, designers, architects, engineers, and all stakeholders have to play important roles in prospering the mosque as it was during the golden age of Islam.